2021
DOI: 10.1007/s13691-021-00516-9
|View full text |Cite
|
Sign up to set email alerts
|

Successful laparoscopic conversion surgery for gastric cancer with para-aortic lymph node metastasis after third-line chemotherapy: a case report

Abstract: We herein reported a case of advanced gastric cancer (GC) with para-aortic lymph node (PALN) metastases who successful achieved downstaging following systemic chemotherapy and underwent curative laparoscopic conversion surgery. A 74-year-old male patient diagnosed with advanced GC and PALN metastases [cT4N3M1(LYM), stage IVA] was administered chemotherapy and immunotherapy for 28 months. After 27 courses of nivolumab as third-line chemotherapy, PALN enlargement was resolved, for which conversion surgery was pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…There are many case reports of CS by ICIs, in which curative resection was achieved with improvement or disappearance of non-curative factors using nivolumab in the third-line of stage IV gastric cancer [6][7][8][9][10][11][12]. In all case reports, R0 resection was performed by CS after confirmation of the disappearance of the lung [6] and liver [7] metastases, peritoneal dissemination [8,9], and reduction of paraaortic lymph node metastases [10][11][12] by imaging findings such as contrast-enhanced CT, magnetic resonance imaging, and positron emission tomography-CT, and the patients did not experience postoperative recurrence. Beom et al found that prognostic factors after CS for stage IV gastric cancer were complete macroscopic resection, chemotherapy response of metastatic sites (complete response/partial response), and change in CEA level [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many case reports of CS by ICIs, in which curative resection was achieved with improvement or disappearance of non-curative factors using nivolumab in the third-line of stage IV gastric cancer [6][7][8][9][10][11][12]. In all case reports, R0 resection was performed by CS after confirmation of the disappearance of the lung [6] and liver [7] metastases, peritoneal dissemination [8,9], and reduction of paraaortic lymph node metastases [10][11][12] by imaging findings such as contrast-enhanced CT, magnetic resonance imaging, and positron emission tomography-CT, and the patients did not experience postoperative recurrence. Beom et al found that prognostic factors after CS for stage IV gastric cancer were complete macroscopic resection, chemotherapy response of metastatic sites (complete response/partial response), and change in CEA level [21].…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, the recommended second-and third-line PD-1 inhibitors for unresectable or recurrent gastric cancer in MSI-high patients are pembrolizumab and nivolumab, respectively. There have been a few reports of conversion surgery (CS) with nivolumab, but none with pembrolizumab to date [6][7][8][9][10][11][12]. We report a case of MSIhigh gastric cancer in which pembrolizumab treatment was successful, CS was performed, and a pathological complete response was obtained.…”
Section: Introductionmentioning
confidence: 96%